Pembentukan Makna Aksi Kolektif Perempuan Kader Tuberculosis di Kutai Timur - Kurniasari, Febriana; Herawati, Erna; Harahap, Junardi (Jayapangus Press, 2025)
Tuberculosis (TB) is an infectious disease and has a strong stigma, but a group of women in East Kutai Regency, have decided to become TB cadres for dozens of years. The TB Cadre's actions are not only to provide counseling to various groups of people, but they also conduct contact investigations and accompany patients until they recover. This study uses a qualitative approach with ethnography method by first conducting a census of 67 TB cadres. After that, conducting participatory observations in the field and in-depth interviews with several TB cadres to TB patients. This study aims to 1) Find out the formation of TB cadres in East Kutai, 2) See the socio-cultural aspects that play a role in the formation of the meaning of women becoming TB Cadres. The results of this study, of the 67 TB Cadres, all are women, dominated by the Bugis and Javanese tribes, and most are housewives. There is a paradigm shift, that East Kutai women currently do not limit their space for action and are more freedom to contribute to the progress of government programs, especially health. The results of observations and interviews also show that there are deep meanings and reasons why women become TBC Cadres, both in terms of religion, beliefs, and family. Factors that play a role in the formation of collective action meaning consist of cultural values, symbols, personal experiences, and gender construction. The formation of meaning is also a process between individuals and groups in interpreting and giving meaning to their experiences, symbols, and cultural practices.